History of Science in the Physics Curriculum: A Directed Content Analysis of Historical Sources - (:unkn) unknown (SPRINGER, 2012)
Although history of science is a potential resource for instructional materials, teachers do not have a tendency to use historical materials in their lessons. Studies showed that instructional materials should be adaptable and consistent with curriculum. This study purports to examine the alignment between history of science and the curriculum in the light of the facilitator model on the use of history of science in science teaching, and to expose possible difficulties in preparing historical materials. For this purpose, qualitative content analysis method was employed. Codes and themes were defined beforehand, with respect to levels and their sublevels of the model. The analysis revealed several problems with the alignment of historical sources for the physics curriculum: limited information about scientists' personal lives, the difficulty of linking with content knowledge, the lack of emphasis on scientific process in the physics curriculum, differences between chronology and sequence of topics, the lack of information about scientists' reasoning. Based on the findings of the analysis, it would be difficult to use original historical sources; educators were needed to simplify historical knowledge within a pedagogical perspective. There is a need for historical sources, like Harvard Case Histories in Experimental Science, since appropriate historical information to the curriculum objectives can only be obtained by simplifying complex information at the origin. The curriculum should leave opportunities for educators interested in history of science, even historical sources provides legitimate amount of information for every concepts in the curriculum.
Keywords: INTERESTINGNESS; PHILOSOPHY; EDUCATION; CLASSROOM; STORIES